2021
DOI: 10.1016/j.jphs.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of the therapeutic potentials of a new series of imidazole derivatives against SARS-CoV-2

Abstract: Owing to the urgent need for therapeutic intervention against the SARS-coronavirus 2 (SARS-CoV-2) pandemic, we employed an in silico approach to evaluate the SARS-CoV-2 inhibitory potential of newly synthesized imidazoles. The inhibitory potential of the compounds against SARS-CoV-2 drug targets - main protease (Mpro), spike protein (Spro) and RNA-dependent RNA polymerase (RdRp) were investigated through molecular docking analysis. The binding free energy of the protein-ligand complexes were estimated, pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…This could be linked to the presence of the delocalized пelectrons in the aromatic ring and the presence of polar compounds in the structure of these compounds. Approximately 20% of essential amino acids are structurally aromatic; interactions involving aromatic compounds are essential to biological recognition, including protein-ligand interaction [9]. Singh [57] reported that aromatic compounds are crucial in drug design as they engender improved efficacy and lead to optimization of the drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be linked to the presence of the delocalized пelectrons in the aromatic ring and the presence of polar compounds in the structure of these compounds. Approximately 20% of essential amino acids are structurally aromatic; interactions involving aromatic compounds are essential to biological recognition, including protein-ligand interaction [9]. Singh [57] reported that aromatic compounds are crucial in drug design as they engender improved efficacy and lead to optimization of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…A high-quality drug candidate should be effective against the therapeutic target and have appropriate ADMET properties at a therapeutic dose [65]. As a result, many in silico models for predicting chemical ADMET properties have been created and it has become advantageous as it reveals a pharmacokinetics-related failure of drugs before proceeding to the clinical phase [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PHASE module of the Schrödinger Suite 2020-3 was used to generate an auto/e-pharmacophore model as previously described 54 . The process was set to generate a maximum of 7 features at a minimum feature-feature distance of 2.00 and the minimum distance between features of the same type was set at 4.00 and donors were set as vectors.…”
Section: Receptor-ligand Complex Pharmacophore Modellingmentioning
confidence: 99%
“…Using in silico studies, many small molecular weight compounds including the existing FDA-approved drugs have proven to be promising therapeutics against 3CL pro of SARS-CoV-2 (Li et al 2020a , b ; Wei-chung et al 2021 ; Johnson et al 2021 ; Al-Bustany et al 2021 ). Some of these compounds have been validated using experimental studies, and they showed considerable inhibitory prowess (pIC50) against 3CL pro of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%